Tanzania Mainland Poverty Assessment - World Bank (World Bank, Washington, DC, 2019)
This report summarizes a comprehensive analysis of poverty and inequality in Tanzania and identifies some priority actions if poverty is to be reduced. The first part is based on the results of the Household Budget Surveys (HBSs) for 2007, 2012, and 2018; several rounds of National Panel Surveys (NPSs); and Demographic Health Survey (DHS) data. It also combines spatial information from the population census and other sources with HBS data to (1) provide a rigorous analysis of the evolution, profile, and determinants of poverty and inequality; (2) exploremovements in and out of poverty and their drivers; and (3) examine the distribution of poverty and living conditions across the country at a detailed geographic level. The second and final part examines the pattern of structural transformation, firm profiles, job creation, and financial inclusion using the rebased GDP figures released in February 2019, plus data from the Statistical Business Register (SBR), Census of Industrial Production (CIP), national accounts, NPS, Integrated Labor Force Surveys (ILFS), and other sources. This executive summary provides an overview ofall the findings.